AB0034 Pharmacokinetics and Safety of BCD-057, Adalimumab Biosimilar Candidate, Compared To Humira in Healthy Volunteers (Results of Phase I Clinical Study). (15th July 2016) - Eremeeva, A.; Fogt, S.; Chernyaeva, E.; Kushakova, A.; Ostroukhova, T.; Ivanov, R.
Abstract : Background: BCD-057 is an adalimumab biosimilar candidate manufactured by BIOCAD, Russia. Full spectrum of physicochemical and preclinical studies showed equivalence of BCD-057 to innovator drug Humira (reference adalimumab, rADA). Objectives: To establish the equivalence of pharmacokinetics and absence of differences in safety of BCD-057 and rADA after the single subcutaneous injection in healthy volunteers. Methods: 94 healthy volunteers were enrolled into the study. 10 of them withdrew consent before drug administration and were not included in analysis. All patients were randomly assigned into 2 groups in a ratio of 1:1 to receive a single subcutaneous injection of BCD-057 or rADA at a dose of 40 mg. The primary endpoints were Cmax and AUC0–∞ after the single adalimumab injection. The secondary PK endpoints included AUC0–1680 h, Tmax, T1/2, Vd, Kel, CL. Adalimumab serum concentrations were evaluated immediately before the injection and after 6, 24, 48, 72, 96, 120, 144, 168, 192, 336, 672, 1008, 1440 and 1680 hours after it. Safety and immunogenicity were also assessed during the study. Results: Pharmacokinetic (PK) analysis demonstrated that 90% CI for the ratio of geometric means of Cmax of adalimumab after single injection of BCD-057 or rADA was 87.48–111.84%. 90% CI for the ratio of geometric means of AUC0-∞ lied within 87.90–117.22%. Both of these facts confirm the bioequivalence of BCD-057 and rADA. There were no statistically significant differences between the groups for all other secondary PK parameters. BCD-057 and rADA were well tolerated. No SAEs were observed during the study. AEs were observed in 9 (22.5%) healthy volunteers in BCD-057 group and in 14 (31.8%) volunteers in rADA group (p=0.463, Fisher's exact test [two-tailed]). They were presented by laboratory abnormalities including leucopenia, neutropenia, monocytosis, monocytopenia, increase in total bilirubin, ALT and AST. All AEs were mild (Grade 1 [CTCAE 4.03]), transient and were not associated with any clinical symptoms. 27 (67.5%) subjects in BCD-057 group and 33 (75.0%) subjects in rADA group (p=0.478, Fisher's exact test [two-tailed]) developed anti-adalimumab antibodies. Neutralizing antibodies to adalimumab were found in 2 (5.0%) volunteers in BCD-057 group and in 5 (11.4%) volunteers in rADA group (p=0.437, Fisher's exact test [two-tailed]). Conclusions: PK, safety and immunogenicity of BCD-057 and rADA after a single subcutaneous administration in healthy volunteers are considered to be equivalent. These data allow to proceed to the subsequent BCD-057 study aimed to assess efficacy and safety in patients with moderate-to-severe plaque psoriasis. References: final study report on phase 1 clinical study of BCD-057 in healthy volunteers. Clinical trial information: NCT02395055 . Disclosure of Interest: A. Eremeeva Employee of: CJSC BIOCAD, S. Fogt Employee of: CJSC BIOCAD, E. Chernyaeva Employee of: CJSC BIOCAD, A. Kushakova Employee of: CJSC BIOCAD, T. Ostroukhova Employee of: CJSC BIOCAD, R. Ivanov Employee of: CJSC BIOCAD